EVALUASI FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA (DSN-MUI) TENTANG AKAD MURABAHAH DAN APLIKASINYA DI PERBANKAN SYARIAH - Hafidz , Abd (CENDEKIA: Jurnal Studi Keislaman, 2015)
Several points in the fatwa of DSN-MUI about buying and selling murabaha are still a debatable case among Islamic economists because it is deemed to violate the sistem of buying and selling murabaha contained in the books of Islamic jurisprudence. And there are some things in the Islamic banking operations that do not apply the fatwa of DSN-MUI.